Influence of Ag Additive to the Spacer Layer on the Structure and Giant Magnetoresistance of Electrodeposited Co/Cu Multilayers. Issue 8 (1st January 2015) - Neuróhr, K.; Péter, L.; Pogány, L.; Rafaja, D.; Csik, A.; Vad, K.; Molnár, G.; Bakonyi, I.
Abstract : In order to explore the possible surfactant effect of Ag on the formation of electrodeposited multilayers, Co/Cu(Ag) multilayers were prepared by this technique and their structure and giant magnetoresistance (GMR) were investigated. The multilayers were deposited from a perchlorate bath with various amounts of Ag + ions in the solution for incorporating Ag atoms into the multilayer stack. Without Ag addition, secondary neutral mass spectroscopy (SNMS) indicated a well-defined composition modulation of the undermost Co/Cu bilayers. However, already at an Ag content as low as 1.8 at.% incorporated, SNMS showed a deterioration of the periodic multilayer structure. In agreement with the SNMS results, superlattice satellites were visible in the X-ray diffraction (XRD) patterns of the multilayers with up to 0.3 at.% Ag. The satellites were, however, very faint even for multilayers without Ag addition, indicating that the multilayers have high interface roughness and/or poor periodicity. In the absence of Ag and at the smallest Ag content investigated by XRD, a strong central multilayer peak and the weak superlattice satellites were complemented by weak diffraction maxima from non-periodic Co and Cu domains. In the Co/Cu(Ag) multilayer containing about 25 at.% Ag, i.e., nearly as much as Cu, XRD found a separate Ag(Cu) phase. In spite of the imperfect layered structure, a multilayer-type GMR behavior was observed in all samples up to about 10 at.% Ag incorporated in the multilayer stack. The GMR magnitude increased for Ag contents up to about 1 at.%, which implies that a small amount of Ag may have a beneficial effect through a slight modification of the layer growth and/or interface formation. However, for higher Ag contents beyond this level, the GMR was reduced in line with the structural degradation revealed by XRD and SNMS. For the highest Ag contents (above about 10 at.%), the GMR exhibited a behavior characteristic of a granular magnetic alloy, in agreement with the results of the structural study.